Anredera cordifolia leaves extract accelerates the wound healing of normal and hyperglycemic rats - Gembira Arkemo Situmorang; Zulham Yamamoto; M. Ichwan; Bambang Prayugo (Universitas Ahmad Dahlan, 2022)
Anredera cordifolia ((Madeira vein (English) or Binahong (Indonesia language)) leaves contain ingredients that promote wound healing. This study aims to determine the effect of Madeira vein leaves ethanolic extract (MLE) on normal and hyperglycemic rat wounds. This is an experimental study using male Wistar rats aged 2-3 months, body weight between 250-300 grams induced by a single injection of streptozotocin dose 60 mg/kg BW intraperitoneally. Rats were divided into 8 groups namely normal without MLE, normal with MLE 2.5% w/v, normal with MLE 5% w/v, normal with MLE 10% w/v, hyperglycemia without MLE, hyperglycemia with MLE 2.5% w/v, hyperglycemia with MLE 5% w/v and hyperglycemia with MLE 10% w/v. Punch biopsy was used to create wounds on the skin of rats with a diameter of 8 mm after the blood glucose level measurement was higher than 200 mg/dL. MLE is applied 3 times a day for 14 days on the wounds. Wound contractions occurred in line with the length of treatment days. In normal skin, the area of the wound had decreased by 22% within three days and to 76% at 14 days after wound creation. On the 14th day of treatment, the wound area of hyperglycemic rats decreased > 60%. The largest wound contraction was found when using MLE 10% w/v. Increasing the MLE dose stimulated better wound contraction/healing than control wounds. Wound healing involves many types and products of cells. Starting with hemostasis, wound healing is followed by inflammatory and proliferative phases to form new tissue, angiogenesis, and matrix formation. The MLE content is beneficial for wound healing in normal and hyperglycemic rats. MLE plays a role in accelerating wound healing in normal and hyperglycemic rats. The MLE dose of 10% w/v provides faster wound healing than the 2.5% and 5% w/v doses.